If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(b + -4) = 12 Reorder the terms: 2(-4 + b) = 12 (-4 * 2 + b * 2) = 12 (-8 + 2b) = 12 Solving -8 + 2b = 12 Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '8' to each side of the equation. -8 + 8 + 2b = 12 + 8 Combine like terms: -8 + 8 = 0 0 + 2b = 12 + 8 2b = 12 + 8 Combine like terms: 12 + 8 = 20 2b = 20 Divide each side by '2'. b = 10 Simplifying b = 10
| -a^6b^8/5 | | w-2/3=61/5 | | 3=w+4/5 | | 5/6(X-3)6 | | 6(Y+7)=5/6(X-3)6 | | 25x^8y/-50x^6y^7 | | x^2-2/5=-9/5x | | x^2-2/5=-9/5 | | 6-4(x+2)=2*x^2 | | X+24X^2=0 | | (x^2+2x+3)(x^2+2x-10)+22=0 | | 2x+20-.2x=20 | | 2.34+023x=6.25 | | (-22/119)(-77/2) | | -0.6+.05x=5.3 | | -0.6+0.5x=5.3 | | -63x-6/-7 | | 5/-4=-19/7 | | 10x-6y=6 | | (-7/11)(-7/11) | | 9x^2-25x+60=0 | | -2x+10=y | | 6p/7 | | 0/-228 | | -4.6-0.1x=-6.1 | | 311.76x^2-3054083x+2311563221=0 | | x*8-5=x | | 26.39t+t^2=90 | | 2x/3+8=x/2-1 | | 7x+1=-6 | | 11x+29=2x+128 | | (3x^2y^3z^2/2y^3z^3)*(3y^-2z^2/9x^-2y^2) |